Formation of Highly Ordered Alloy Nanoparticles Based on Precursor-Filled Latex Spheres - Vogel, Nicolas; et al. (Chemistry of Materials, 2012)
An experimental approach is presented, allowing the preparation of substrate supported, hexagonally arranged metallic alloy nanoparticles with narrow size distributions, well-defined interparticle distances, and controlled chemical composition. The method is based on miniemulsion polymerization and isotropic plasma etching. Polystyrene (PS) and poly(methyl methacrylate) (PMMA) colloids in the present study containing Fe- and Pt-precursor complexes in a predefined ratio are deposited onto hydrophilic Si/SiO2 substrates by dip-coating, forming a highly ordered monolayer. Contrary to colloidal lithography, here, precursor-filled polystyrene colloids serve as carriers for the alloy forming elements. After reactive ion etching and annealing, hexagonally ordered arrays of crystalline FePt nanoparticles are formed exhibiting the desired 1:1 Fe-Pt ratio, as revealed by detailed analysis after each preparation step. Formation of stoichiometric binary alloy FePt nanoparticles is confirmed by determining magnetic hysteresis loops, as well as applying aberration-corrected high-resolution transmission electron microscopy.
Keywords: miniemulsion; colloid monolayer; FePt; nanoparticles; colloidal lithography